Progression-free survival in patients with 68Ga-PSMA-PET-directed SBRT for lymph node oligometastases. (3rd October 2021) - Werensteijn-Honingh, Anita M.; Wevers, Anne F. J.; Peters, Max; Kroon, Petra S.; Intven, Martijn; Eppinga, Wietse S. C.; Jürgenliemk-Schulz, Ina M.
Abstract: Background: Prostate cancer oligometastatic disease can be treated using stereotactic body radiotherapy (SBRT) in order to postpone start of systemic treatments such as androgen deprivation therapy (ADT). 68Ga-PSMA-PET/CT imaging allows for diagnosis of oligometastases at lower PSA values. We analysed a cohort of patients with prostate cancer lymph node oligometastases detected on PSMA-PET/CT. Materials and methods: Ninety patients with metachronous oligometastatic prostate cancer received SBRT for 1–3 lymph node metastases diagnosed on 68Ga-PSMA-PET/CT. The primary end point was progression free survival (PFS), with disease progression defined as occurrence of either target lesion progression, new metastatic lesion or biochemical progression. Secondary outcomes were biochemical PFS (BPFS), ADT-free survival (ADT-FS), toxicity and quality of life (QoL). Baseline patient characteristics were tested for association with PFS and a preliminary risk score was created. Results: Median follow-up was 21 months (interquartile range 10–31 months). Median PFS and BPFS were 16 and 21 months, respectively. Median ADT-FS was not reached (73% (95%-CI 62–86%) at 24 months). In multivariable analysis, younger age, higher PSA prior to SBRT and extrapelvic location were associated with shorter PFS. Grade 1 fatigue was the most predominant acute toxicity (34%). Highest grade toxicity was grade 2 for acute and late events. QoL analysis showed mild, transient increase in fatigue at 1–4 weeks after SBRT. Conclusion: A median PFS of 16 months was attained after SBRT for patients with PSMA-PET positive oligometastatic lymph nodes from prostate cancer. Higher pre-SBRT PSA, younger age and extrapelvic location were found to be predictors of shorter PFS.